Pembelajaran SBdP Melalui Sistem Daring Pada Kelas V SDN Plumbungan Kecamatan Gabus Kabupaten Pati - Nisaul Firdaus; Prasena Arisyanto; Aries Tika Damayani (STKIP Andi Matappa Pangkep, 2021)
The background that drives this research is the Covid-19 outbreak that affects people's lives in various fields, one of which is education. Where in the field of education is held online learning. This can affect SBdP learning activities, learning that is identical to the practice of art and dance. This research method is qualitative. Methods of data collection using observation, interviews, documentation. The results of the study show that online SBdP is preparing tools that support learning. To overcome the obstacles experienced by teachers and students, the school cooperates with the village government and the community to carry out face-to-face learning activities in one of the residents' homes, of course by paying attention to health protocols. Implementation of the opening, core, closing SBdP learning activities briefly, adjusted to material needs. The application used is Whatsapp Group. Assessment of online learning outcomes refers to three aspects of spiritual and affective, cognitive, psychomotor. The conclusion of this study is that the preparation, implementation and results of the SBdP learning assessment through the online system in class V SDN Plumbungan are adapted to the conditions of the covid-19 pandemic, activities are carried out virtually because considering the health protocol requires not crowding.